An evaluation of conventional and nature-based technologies for controlling antibiotic-resistant bacteria and antibiotic-resistant genes in wastewater treatment plants - Hazra, Moushumi; Watts, J. E. M.; Williams, J. B.; Joshi, H. (Elsevier, 2024)
Antibiotic resistance is a globally recognized health concern which leads to longer hospital stays, increased morbidity, increased mortality, and higher medical costs. Understanding how antibiotic resistance persists and exchanges in environmental systems like soil, water, and wastewater are critically important for understanding the emergence of pathogens with new resistance profiles and the subsequent exposure of people who indirectly/ directly come in contact with these pathogens. There are concerns about the widespread application of prophylactic antibiotics in the clinical and agriculture sectors, as well as chemicals/detergents used in food and manufacturing industries, especially the quaternary ammonium compounds which have been found responsible for the generation of resistant genes in water and soil. The rates of horizontal gene transfer increase where there is a lack of proper water/wastewater infrastructure, high antibiotic manufacturing industries, or endpoint users – such as hospitals and intensive agriculture. Conventional wastewater treatment technologies are often inefficient in the reduction of ARB/ARGs and provide the perfect combination of conditions for the development of antibiotic resistance. The wastewater discharged from municipal facilities may therefore be enriched with bacterial communities/pathogens and provide a suitable environment (due to the presence of nutrients and other pollutants) to enhance the transfer of antibiotic resistance. However, facilities with tertiary treatment (either traditional/emerging technologies) provide higher rates of reduction. This review provides a synthesis of the current understanding of wastewater treatment and antibiotic resistance, examining the drivers that may accelerate their possible transmission to a different environment, and highlighting the need for tertiary technologies used in treatment plants for the reduction of resistant bacteria/genes.